Rapport au roi, fait par la commission créée par l'ordonnance du 1er septembre 1825 - Lévis, Pierre-Marc-Gaston, duc de, 1764-1830 (De l'Impr. royale, 1826)
Report of the French royal commission established to determine amounts Haiti would be obliged to award former colonists of Saint-Domingue in compensation for their losses.